New Results on Testing Against Independence with Rate-Limited Constraints - Espinosa, Sebastian; Silva, Jorge F.; Piantanida, Pablo (2019 IEEE Global Conference on Signal and Information Processing (GlobalSIP), 2019)
This work studies error exponent limits in hypothesis testing (HT) in a distributed scenario with partial communication constraints. We derive general conditions on the Type I error restriction under which the error exponent of the optimal Type II error has a closed-form characterization for the task of testing against independence. We show that the error exponent is preserved for a family of decreasing Type I error restrictions. Complementing this analysis, new expressions are derived to bound the optimal Type II error probability for a finite number of observations. These bounds shed light about the velocity at which error exponent limits are attained with the number of samples.